Effective removal of cationic methylene blue dye using nano‐hydroxyapatite synthesized from fish scale bio‐waste. Issue 3 (4th January 2021) - Swamiappan, Sathiskumar; Ganesan, Sivarasan; Sekar, Vanaraj; Devaraj, Sabarinathan; Subramanian, Arulmani; Ponnusamy, Vinoth Kumar; Kathirvel, Preethi
Abstract: Nano‐hydroxyapatite (NHAp) with a novel rod shape was synthesized from an economical and easily accessible Labeo rohita fish scale bio‐waste by facile and straightforward alkaline heat treatment method. The purity, functionality, morphology, and surface area of the green synthesized NHAp powder were well‐characterized via X‐ray diffraction (XRD), Fourier‐transform infrared (FT‐IR) spectroscopy, transmission electron microscopy (TEM), and Brunauer‐Emmett‐Teller (BET). The TEM and BET results indicate that the apatite is prepared as a rod‐like particle and highly porous with high surface area (112.36 m 2 g −1 ). The NHAp powder was used for the adsorptive removal of cationic dye‐methylene blue (MB) from the aqueous samples. Batch experiments were performed to evaluate the mechanism of adsorption and kinetic models. The NHAp achieved an enhanced adsorption efficiency (666.67 mg g −1 ) for the adsorption process. The obtained results perfectly obeyed the pseudo‐second‐order model, and the Langmuir isotherm exhibited an excellent relationship with the experimental data. Furthermore, thermodynamic studies reveal that the adsorption process was exothermic and spontaneous. Thus, the results proved that Labeo rohita fish scale bio‐waste derived NHAp can be inventively utilized as a cost‐effective and eco‐friendly adsorbent for wastewater treatment. Abstract : Effective dye removal using nano‐hydroxyapatite synthesized from Labeo rohita fish scale bio‐waste.